Volume 4A: Combustion, Fuels and Emissions 2015
DOI: 10.1115/gt2015-42122
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Emissions From the Use of Alternative Aviation Fuels

Abstract: Alternative fuels for aviation are now a reality. These fuels not only reduce reliance on conventional petroleum-based fuels as the primary propulsion source, but also offer promise for environmental sustainability. While these alternative fuels meet the aviation fuels standards and their overall properties resemble those of the conventional fuel, they are expected to demonstrate different exhaust emissions characteristics because of the inherent variations in their chemical composition resulting from the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…10,14,17,19 Most other data were collected near the engine exit using a sampling protocol which does not capture the volatile sulfur and organic particles formed in the downstream plume. [6][7][8][9][10][11][12][14][15][16][18][19][20][21]23 In addition, some data sets only provide normalized EIs rather than actual emissions, thus further restricting their usefulness for comparison to other work. Table S4 in the Supporting Information shows the emissions reductions associated with the use of the FT jet fuels and blends evaluated in our study as compared to other alternative fuel measurements reported in the literature.…”
Section: Emissions Reduction Discussionmentioning
confidence: 99%
“…10,14,17,19 Most other data were collected near the engine exit using a sampling protocol which does not capture the volatile sulfur and organic particles formed in the downstream plume. [6][7][8][9][10][11][12][14][15][16][18][19][20][21]23 In addition, some data sets only provide normalized EIs rather than actual emissions, thus further restricting their usefulness for comparison to other work. Table S4 in the Supporting Information shows the emissions reductions associated with the use of the FT jet fuels and blends evaluated in our study as compared to other alternative fuel measurements reported in the literature.…”
Section: Emissions Reduction Discussionmentioning
confidence: 99%
“…Total particle number (A) and particle mass (B) emission index for the different thrust settings and fuels (EEPS, 5.6 -200 nm).It must be noted that the impact of the fuel composition on the particle reduction potential is strongly depending on the jet engine used. Chan et al[27] used a GE CF-700-2D-2 turbofan engine (20 kN) for testing the emissions from three different alternative fuels in comparison to regular Jet A-1. Their fuels "CH-SKA" and "FT-SPK" are chemically comparable to the ReadiJet and ATJ fuels of this experiment.…”
mentioning
confidence: 99%